Algal Polysaccharides as Therapeutic Agents for Atherosclerosis - Patil, Nikita P.; Le, Victoria; Sligar, Andrew D.; Mei, Lei; Chavarria, Daniel; Yang, Emily Y.; Baker, Aaron B. (Frontiers in Cardiovascular Medicine, 2018)
Seaweed-derived polysaccharides including agar and alginate, have found widespread applications in biomedical research and medical therapeutic applications including wound healing, drug delivery, and tissue engineering. Given the recent increases in the incidence of diabetes, obesity and hyperlipidemia, there is a pressing need for low cost therapeutics that can economically and effectively slow the progression of atherosclerosis. Marine polysaccharides are have been consumed by humans for millennia and available in large quantities at low cost. Polysaccharides such as fucoidan, laminarin sulfate and ulvan have shown promise in reducing atherosclerosis and its accompanying risk factors in animal models. However, others have been tested in very limited context in scientific studies. In this review, we explore the current state of knowledge for these promising therapeutics and discuss the potential and challenges of using seaweed derived polysaccharides as therapies for atherosclerosis.